A sensorial foray into architecture - Kristanti Dewi Paramita (ARSNET, 2022)
Discussion of a sensory-driven architecture emphasises the need for a deeper and more holistic understanding of space. The collection of articles in this issue of ARSNET presents a variety of methods for engaging with the sensorial experience. These articles explore the process of measuring, interpreting, tracing, and constructing the spatial elements and spatial processes driven by sensorial stimulants, driving different projections of space. From the emergence of architecture that is more responsive to the diverse and subjective body needs in space to architecture that responds towards natural qualities as well as natural processes. Some articles also enable propositions of architectural form and programming with sensory-induced spatialities and temporalities. Through such projections, the issue creates multiple possibilities for sensory-driven design objectives which transcend contexts, practices and users, significantly expanding the sensory architecture discourse.